Digestibility of Native Chicken Rations Containing Fermented Banana Peels - Suariani, Luh; I Gusti Agus Maha Putra Sanjaya; I Nyoman Kaca; Gede Ari Supastiawan; I Wayan Richo Yasa (International Journal of Scientific Multidisciplinary Research, 2023)
Improving the performance of super native chickens must be balanced by improving the ration. The ingredients used do not need to be “expensive” but are of good quality and readily available throughout the year. One of the feed ingredients that is widely available and is a waste is banana peel. Banana peels contain 3.63% nutrients, 2.52% crude fat, 18.71% crude fiber, 7.18% calcium, and 2.06% phosphorus. In addition to high crude fiber, banana peels also contain antinutrients in the form of tannins, hence the need for fermentation. To see the quality of the ration, it is necessary to test the digestibility. This research was carried out from March to July 2023. The design used in this study was a completely randomized design (CRD) with 5 (five) treatments and 3 (three) replicates. The treatments were as follows: R0 (ration without the addition of fermented banana peel flour/TKPF), R1 = (2.5% TKPF), R2 = 5% TKPF, R3 = 7.5% TKPF, R4 = 10% TKPF. Variables observed were N retention, protein digestibility, crude fiber digestibility, and organic matter digestibility. The results showed that the provision of fermented banana flour in the ration of native chickens significantly (P <0.01) influenced the digestibility of crude protein, crude fiber digestibility, digestibility of organic matter, and N retention of native chicken rations. The best results were obtained in the R2 treatment (5% Fermented Banana peel flour), where the crude protein digestibility gave results of 76.11%, crude fiber digestibility of 45.12%, organic matter digestibility of 70.09%, and N retention of 75.82%